Mealtime interaction between mothers and their young ones with cerebral palsy - Nina Sivan; Prathima S; Swapna N (Journal of All India Institute of Speech and Hearing, 1970)
The aim of this study was to investigate the mealtime interaction between mothers and their young children with cerebral palsy (CP). Three groups of participants were included in the study. The mothers of thirteen young children with CP, the mothers of seventeen children with CP and associated ID and the mothers of seventeen typically developing children in the age group of 2.6 to 3.6 years participated in the study. A questionnaire pertaining to mother initiated and child initiated communication during mealtime wasdeveloped, validated and administered on the participants. The responses were documented, scored and statistically analyzed. The results revealed that the mealtime interaction initiated by the mother was signi cantly different across groups, wherein the mothers of the group of typically developing children interacted more often to their children when  compared to the mothers of children with CP. The mealtime interaction initiated by the mothers of children with both CP and ID was the least. Further, there was no signi -cant dierence found in the child initiated communication across the groups. It was found that the typically developing children initiated communication using speech and children with CP and CP with ID used the nonverbal mode primarily. It can be concluded that mothers of children with CP interact less and are less responsive to their child's communication attempts during mealtime. The study throws light on the importance of facilitating mother child interaction during mealtime in feeding therapy sessions, which is a goodplatform for improving their overall feeding and communication abilities